Perception of the benefits of companion animals during the time of quarantine by COVID-19 in a sample of inhabitants of the city of Medellín, Colombia (2023)
The present study aimed to identify the perception of the benefits derived from the company of pets during the quarantine by COVID-19 in a sample of the Medellín city population, Colombia. A quantitative, descriptive, ex post facto study was used, with the participation of 141 people, 73 % women (n=102) and 27 % men (n=39), with an average age of M=35.2 (SD =8.4). The variables of human-animal interaction, emotional closeness with the pet, physical and psychological benefits, and perceived cost were evaluated through an ad-hoc Likert-type questionnaire with Alpha Cronbach 9.79. The results indicate that the study participants have a high perception of the psychological and physical benefits and a high emotional closeness with their pets during the quarantine by COVID-19. This perception was independent of the variables of gender, age, occupation, educational level, economic level, and type of pet. The perception of physical benefits was related to the type of pet, being higher in the case of dogs. It is concluded that the company of pets represented a positive contribution to the mental health of the study participants in the situation of social distancing during quarantine.